Numerical investigations of repairable dissipative bolted fuses for earthquake resistant composite steel frames. (15th January 2017) - Valente, Marco; Castiglioni, Carlo A.; Kanyilmaz, Alper
Highlights: Potential damage concentrates in replaceable dissipative bolted fuses. The effects of different geometrical characteristics of the fuse are analyzed. The seismic performance of steel frames with bolted fuses is investigated. Frames with bolted fuses exhibit high energy dissipation capacity. Abstract: This study presents the main results of the numerical investigations carried out on an innovative repairable fuse device for dissipative beam-to-column connections in moment-resisting composite steel frames. The fuse consists of steel plates bolted to the web and bottom flange of the beam with a specifically detailed gap in the concrete slab. The behavior of the fuse device is studied by means of two different numerical approaches. Numerical analyses performed on detailed three-dimensional finite element models of beam-to-column sub-assemblages show that potential damage concentrates only in the fuse section, without any significant damage in the other structural elements. Repair work, if needed, is therefore limited to the replacement of the fuses only. The effects of some geometrical characteristics of the flange plates on the behavior of the fuses are investigated. In order to extend the results of the numerical analyses to multi-storey frames subjected to seismic excitations, simple numerical models of the device are developed and calibrated through the experimental results of laboratory tests. Non-linear dynamic and static analyses are performed on multi-storey composite steel frames and the effectiveness of the fuse devices is evaluated. The influence of the main mechanical characteristics of the different devices on the seismic performance of several composite steel frames is also discussed for various ground motion intensity levels. Experimental and numerical results show that it is possible to successfully dissipate energy and concentrate plasticity by means of the fuse system, along with simple and cost effective repairability.